Diterpenoids from the Whole Plant of Lagochilus platyacanthus - Zhang, Cheng-Gang; Wang, Lu; Lu, Ye; Ye, Zi; Han, Zhu-Zhen; Xu, Hong; Chou, Gui-Xin (Planta Medica, 2015)
Five new diterpenoids, lagoditerpenes A–E (1–3, 5, 6), along with ten known compounds were isolated from the herb of Lagochilus platyacanthus. The absolute structures of 1–4 and 6 were unequivocally elucidated by extensive spectroscopic analyses in association with single-crystal X-ray diffraction, in which compounds 1 and 2 were the epimers at C-13. Furthermore, in in vitro assays, compounds 1, 2 and 6 showed moderate hemostatic activities by shortening the values of activated partial thromboplastin time.
Keywords: Lagochilus platyacanthus; Lamiaceae; diterpenoids; hemostatic